1997
DOI: 10.1055/s-2007-1015379
|View full text |Cite
|
Sign up to set email alerts
|

Metabolische Charakterisierung von Ovarialtumoren mit der Positronen-Emissions-Tomographie und F-18-Fluordeoxyglukose

Abstract: Enhanced glucose metabolism of ovarian cancer enables PET diagnosis with a sensitivity of 83%. An intensive FDG uptake in inflammatory processes resulted in a specificity of only 54% in this study. The high sensitivity of PET for malignant tumours may be useful in the detection of recurrent ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
14

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 0 publications
2
9
1
14
Order By: Relevance
“…The role of whole body FDG PET in the diagnosis and staging of primary ovarian tumors is still a matter of debatel. Early studies have shown sensitivities and specificities of 83-86% and 54-86%, respectively (32,33). A recent study has demonstrated that the routine use of FDG PET is unsuitable as a diagnostic imaging procedure for lesion characterization, evaluation of the extent of the disease and the relationship with the adjacent organs (34).…”
Section: Discussionmentioning
confidence: 99%
“…The role of whole body FDG PET in the diagnosis and staging of primary ovarian tumors is still a matter of debatel. Early studies have shown sensitivities and specificities of 83-86% and 54-86%, respectively (32,33). A recent study has demonstrated that the routine use of FDG PET is unsuitable as a diagnostic imaging procedure for lesion characterization, evaluation of the extent of the disease and the relationship with the adjacent organs (34).…”
Section: Discussionmentioning
confidence: 99%
“…Las imágenes diagnósticas de la PET se obtienen mediante la administración intravenosa de un radiofármaco, que es la unión de un isótopo radioactivo con una molécula determinada; pasados 45-60 minutos se realiza la adquisición de imágenes del cuerpo completo en una tomogammacámara PET. En la práctica clínica diaria, la molécula que se utiliza es la 2-Fluoro-D-Desoxiglucosa (FDG) que va unida al 18 F, isótopo radiactivo emisor de positrones de período de semidesintegración muy corto (110 minutos). La 18 F-FDG es un análogo de la glucosa y es captada tanto por las células normales como por las tumorales, pero no sigue el ciclo bioquímico normal de la glucosa, por lo que queda atrapada en su interior.…”
Section: Introductionunclassified
“…En la práctica clínica diaria, la molécula que se utiliza es la 2-Fluoro-D-Desoxiglucosa (FDG) que va unida al 18 F, isótopo radiactivo emisor de positrones de período de semidesintegración muy corto (110 minutos). La 18 F-FDG es un análogo de la glucosa y es captada tanto por las células normales como por las tumorales, pero no sigue el ciclo bioquímico normal de la glucosa, por lo que queda atrapada en su interior.…”
Section: Introductionunclassified
See 2 more Smart Citations